2017
DOI: 10.1016/j.yjmcc.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in the fetal cardiac response to maternal nutrient restriction

Abstract: Poor maternal nutrition causes intrauterine growth restriction (IUGR); however, its effects on fetal cardiac development are unclear. We have developed a baboon model of moderate maternal undernutrition, leading to IUGR. We hypothesized that IUGR affects fetal cardiac structure and metabolism. Six control pregnant baboons ate ad-libitum (CTRL)) or 70% CTRL from 0.16 of gestation (G). Fetuses were euthanized at C-section at 0.9G under general anesthesia. Male but not female IUGR fetuses showed left ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 144 publications
9
39
0
Order By: Relevance
“…Interestingly, there was no difference in COL3A mRNA expression between the Control and LGUN groups; however, the increase in COL1A:COL3A in the LGUN group suggests decreased cardiac contractility and compliance (Wei et al 1999). Furthermore, despite the previously reported sex effect, our results are consistent with an increased prevalence of myocardial fibrosis in the hearts of IUGR male non-human primates (Muralimanoharan et al 2017). These data along with the changes to contractility proteins (PLB and Troponin I) in the present study may explain the emergence of dysfunction in the right ventricle after birth in the IUGR non-human primate (Kuo et al 2017a).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, there was no difference in COL3A mRNA expression between the Control and LGUN groups; however, the increase in COL1A:COL3A in the LGUN group suggests decreased cardiac contractility and compliance (Wei et al 1999). Furthermore, despite the previously reported sex effect, our results are consistent with an increased prevalence of myocardial fibrosis in the hearts of IUGR male non-human primates (Muralimanoharan et al 2017). These data along with the changes to contractility proteins (PLB and Troponin I) in the present study may explain the emergence of dysfunction in the right ventricle after birth in the IUGR non-human primate (Kuo et al 2017a).…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, despite the previously reported sex effect, our results are consistent with an increased prevalence of myocardial fibrosis in the hearts of IUGR male non‐human primates (Muralimanoharan et al . ). These data along with the changes to contractility proteins (PLB and Troponin I) in the present study may explain the emergence of dysfunction in the right ventricle after birth in the IUGR non‐human primate (Kuo et al .…”
Section: Discussionmentioning
confidence: 97%
“…The placenta influences the sex-specific embryonic responses to the maternal environment, [81][82][83][84] and has a role in conferring biased susceptibility to gestational insults. [80,85,86] In humans, for example, male fetuses exposed to intrauterine adversity are more vulnerable than females [87] and are 4-8 times more likely than females to present neurodevelopmental disorders.…”
Section: Embryos Exhibit Sex-specific Responses To the Maternal Envirmentioning
confidence: 99%
“…The nature of these postnatal changes fit with the fibrosis demonstrated in the article reviewed here and Muralimanoharan et al . (). The pattern of vascular distribution observed in IUGR offspring is reminiscent of the changes that occur in fetuses challenged by hypoxia or undernutrition (Cohn et al .…”
mentioning
confidence: 97%
“…Unfortunately, the study was not able to determine sexually dimorphic differences. A study of left ventricular (LV) myocardial tissue in IUGR fetuses of baboons fed 70% of control diet found that in males, but not females, LV fibrosis inversely correlated with birth weight (Muralimanoharan et al 2017). It found differences in expression of fetal myocardial microRNAs (miRNAs) between male and female fetuses within both control and IUGR baboon groups.…”
mentioning
confidence: 99%